The Effect of Teaching Exercises by Means of Aids in Some of Biomechanical Variables and the Achievement of Shot Put for Girls Students - Mayassa Abd Ali Kahdim Sebti (Journal of Global Pharma Technology, 2016)
The study aimed to identify the effect of educational exercises related to the aids in the development of some biomechanical variables and the achievement of the weight-effectiveness of the students. The study also hypothesis that there are statistically significant differences between the results of the tribal and remote tests of the experimental and control groups. The researcher used the experimental method (and the design of the two equal groups) for the suitability and the nature of the research on the research community of the first stage students (40) students in the Department of Physical Education and Sports Sciences / Faculty of Education for Girls / University of Kufa for the academic year (2016 - 2017) Randomization The sample was randomly divided and distributed by lottery method to two groups of 15 students for both experimental and control groups. After conducting the pre and posttests, the data were collected and processed statistically to extract the results through which the most important conclusions were reached:There are statistically significant differences between the results of the pretest and the posttest of the achievement of the shot put and the experimental and control groups, as well as when comparing the results of the tests of the control and experimental groups and for the benefit of the experimental group.The use of educational aids to teach the activity of the shot put and greatly develop the skill mentioned.The results showed that there were differences between the results of the post and pretests of the experimental research group, except for variable high aviation point, since there were no differences between the results of the pre and posttests.There were significant differences between the results of the pre- and post-test tests of the control group in the investigated biomechanical variables, while there were no significant differences in high aviation point.There were no significant differences between the two post-experimental tests of the experimental and control groups in variable high aviation point, while the biomechanical variables detected showed significant differences in favor of the experimental group.Keywords: Teaching exercises, Means of aids, Biomechanics and Shot put.